The New Politics of Financing the UN - McDermott, Anthony. author. aut Link
VII, 213 p.
Keywords: The UN has suffered from its earliest days as a result of persistent financial problems, which left it on the edge of apparent bankruptcy. This book looks at the history of the regular and peace-keeping budgets. It focuses on the role of the US, simultaneously the UN's biggest contributor of funds and its largest debtor. It examines possible solutions against the background today of the UN attempting to reform itself to meet the challenges posed by globalization and an increasing number of civil wars.